Substitute equation (1) into equation (2) and solve for x.

\(x + 2(-2x) = 9 x - 4x = 9 -3x = 9 x = -3\)

Substitute \(x = -3\) into equation (2) and solve for y.

\(y = -2 \times (-3) y = 6\)

Thus, the solution is (-3, 6).

Question

asked 2020-12-28

Solve the system: \(\begin{cases}3x+y=9\\2x-y=1\end{cases}\)

asked 2021-02-19

Solve the system of equations. \(\{(x,+,4y,=,-2),(-2x,+12y,=,9):\}\)

asked 2020-12-22

Solve \(\begin{cases}2x+3y=-1\\6x+3y=-9\end{cases}\)

asked 2021-06-16

Solve the system by clennaton \(2x-y=0\)

\(3x-2y=-3\)

The solution is ( . )